2005
DOI: 10.1159/000086895
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of nondisjunction in human spermatogenesis

Abstract: A reduction in recombination in the pseudoautosomal region is associated with an increased frequency of aneuploid 24,XY human sperm. Similarly, individuals with paternally derived Klinefelter syndrome (47,XXY) also have a paucity of recombination in the chromosomes that have undergone nondisjunction. Meiotic studies using newly developed immunocytogenetic techniques have demonstrated errors of chromosome synapsis and significantly reduced recombination in infertile men with nonobstructive azoospermia. These me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…This point is of specific interest as only meiotic divisions were exposed to EE2 in our study. Although such disturbances can affect all chromosomes, it has been observed that chromosomes with fewer recombination sites, or chiasma, exhibit higher levels of aneuploidy in gametes (56)(57)(58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…This point is of specific interest as only meiotic divisions were exposed to EE2 in our study. Although such disturbances can affect all chromosomes, it has been observed that chromosomes with fewer recombination sites, or chiasma, exhibit higher levels of aneuploidy in gametes (56)(57)(58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Defects may include structural chromosome abnormalities, such as translocations, Y chromosome microdeletions, and single or double strand DNA breaks, or numerical chromosome abnormalities, such as Klinefelter's syndrome or sperm chromosome aneuploidy [8,16,23,26]. Gene mutations and polymorphisms can affect any of the approximately 2000 proteins involved in spermatogenesis, and epigenetic alterations may also affect protein expression and activity [5,8].…”
Section: A Brief Overviewmentioning
confidence: 99%
“…Since, however, post-meiotic cells were sparse and varied individually in their presence and ploidy among the KS patients, the results did not reach significance level and thus our deductions are restricted. Theoretically, the expected rate of aneuploidy in the setting of 47,XXY meiosis is up to 50 % [46,47]. However, the percentages of aneuploidy values in the testes of KS men reported by others reached 10-20 % [5,8,9].…”
Section: Discussionmentioning
confidence: 89%